Microbial development and interaction in blue veined cheeses - Knox, Alison Margaret (University of the Free State, 2004)
From the extensive literature review given in Chapter 1, it was evident that blue-mould cheeses are unique in terms of the flavour, aroma, texture and microbial developments that take place during production and maturation. Despite surface mould-ripened cheeses only representing a small portion of the annual world cheese production, their popularity is increasing worldwide making it important to study their microbiological, biochemical and technological properties. Consequently, the aims of this study were to identify a medium suitable for the isolation and enumeration of yeasts in the presence of moulds, elicit the establishment, growth and survival of yeasts during the processing and ripening of blue-mould cheeses, to follow the interaction between the microbiota present and to determine their influence on each other. In addition, since the interactive development of the different microbiota also affects the final cheese product, the technological changes were determined. As Brevibacterium linens plays a substantial role on the quality of blue veined cheese, various methods were applied as a means of inhibiting the growth and development of the species. The enumeration of yeasts in the presence of moulds proved to be difficult since the yeasts are easily overgrown by the rapid spreading of moulds. We therefore aimed to find a medium that not only supported the growth of the yeasts, but also inhibited mould growth to such an extent that the isolation and enumeration of the yeasts could be performed with relative ease. Ten different selective media with anti-mycotic properties were evaluated and compared statistically using analysis of variance (ANOVA) and the TukeyKramer multiple comparison test, for their ability to suppress the growth and spreading of moulds and to enhance the enumeration and recovery of yeasts from blue-mould cheeses. No significant differences in quantitative data obtained on Rose-Bengal Chloramphenicol Agar (RBCA), Dichloran RoseBengal Chloramphenicol Agar (DRBC), Dichloran 18% Glycerol Agar (DG18), and Molybdate agar with 10% Sodium Propionate (MES) were detected by four of the collaborating laboratories whereas one laboratory found RBCA to be superior for yeast enumeration. DG18 and Malt Extract Agar with Biphenyl (MEB), however, were ranked superior based on qualitative results compared to the other media, attributed to distinctive individual yeast colonies and mould inhibition. Yeasts are one of the main microbial groups that occur during the ripening of blue veined cheese varieties, originating as post-pasteurisation contaminants. In Chapter 3 the development of yeasts derived mainly from the dairy environment and their establishment during the ripening process was examined. Yeast species isolated and identified corresponds with those obtained by other researchers on similar cheese varieties. A 10 to 100 fold difference in yeast numbers were observed during the ripening period between the exterior and interior. Debaryomyces hansenii predominated in the present study. This was due to its ability to produce extracellular proteases and lipases and the species high tolerance towards low temperatures and high salt concentrations. Although yeasts are one of the major microbial groups present in blue veined cheese other microorganisms like Penicillium roqueforti and several different bacterial genera are also frequently encountered. All of these organisms collectively contribute to the final flavour and aroma of the product based on interactive proliferation. Consequently it was necessary to study the interactions between these microorganisms to improve our understanding of the ripening process and the contribution each makes to the process. Studies revealed that various interactions occurred between yeasts and P. roqueforti, as well as yeasts and bacteria essential to the final outcome of the cheese product. The majority of yeast-bacterial interactions were neutral, although some interactions were antagonistic and others stimulative. Debaryomyces hansenii was the most stimulatory yeast species towards bacterial isolates while Torulospora delbrueckii was the most antagonistic. All three microbial groups studied dominated throughout the ripening period and were present in meaningful numbers at the end of the ripening period. The use of Radical water™ to reduce or inhibit B. linens growth yielded limited results. A treatment time of 90 mm with Radical water™ for the wooden pallets used for storage of the blue-mould cheese during maturation was determined to be optimal for inhibiting or reducing B. linens growth on these pallets and thus reducing the spread to the cheese. Despite this being a time consuming process, the treatment of the pallets with Radical water™ has since been implemented in the cheese factory. The addition of the yeast D. hansenii did not reduce the presence of B. linens, but did however improve the overall texture and flavour of the final cheese product. While covering the whole cheese with a layer of plastic to create an anoxic layer around the cheese, proved to be the most effective means of controlling B. linens, time constraints proved it not an economically viable option. Further investigations based on the inhibition of B. linens included the application of yeasts and probiotics as possible bio-control agents. None of the dairy associated yeasts tested proved to be successful, whereas Lactobacillus rhamnosus and Bifidobacterium lactis, two typical probiotic species applied in dairy products, showed inhibitory effects against B. linens when tested using the spot-on-lawn assay.
Thesis (Ph.D. (Microbial, Biochemical and Food Biotechnology))--University of the Free State, 2004
Keywords: Blue-mould cheese; Yeast development; Interaction; Inhibition; Brevibacterium linens; Lactobacillus rhamnosus; Bifidobacterium lactis; Yeast; Brevibacterium; Cheesemaking -- South Africa; Cheese -- Microbiology -- South Africa